Body image diversity in the media: A content analysis of women's fashion magazines. (3rd January 2018) - de Freitas, Catarina; Jordan, Helen; Hughes, Elizabeth K.
Abstract: Issue addressed: The narrow representation of body image in the media has been linked to body dissatisfaction, particularly among readers of women's fashion magazines. Some countries have made efforts to improve body image diversity in the media and the fashion industry. This has included attempts to regulate minimum body size of models (eg, Israel, France), and the development of codes of practices such as the Australian Industry Code of Conduct on Body Image. However, there is little evidence of whether these efforts have impacted media content. Method: This study aimed to gauge the state of body image diversity in the print media 5 years after the introduction of the Australian Code of Conduct via a content analysis of 13 Australian women's fashion magazines published in 2015. Results: Results revealed low levels of diversity in body size, ethnicity and age among models depicted in fashion magazine images. Models were predominantly young, white and underweight. Conclusion: The results suggest that efforts to improve body image diversity have had little impact on print media. Further research is needed to understand the barriers to increased diversity in the representation of body image in the media so that the industry and regulatory bodies can further address this important issue. This is increasingly pressing given the proliferation of content now enabled through online media platforms.